KEUNGGULAN DIGITAL BANK MANDIRI : ANALISIS VRIO - Onoyi, Nona Jane; Muharya, Agil (Mount Hope Management International Journal, 2025)
This article analyzes Bank Mandiri's digital competitive advantage using the VRIO (Value, Rarity, Imitability, Organization) framework. Bank Mandiri, as one of the largest banks in Indonesia, has successfully utilized digital transformation through the Livin by Mandiri service. This study uses a qualitative approach with literature study and document analysis methods, collecting data from Bank Mandiri's annual report, official publications, news articles, and studies related to digital transformation in the banking industry. Secondary data used in this study were validated through triangulation to ensure the accuracy and reliability of the findings. The results of the VRIO analysis show that Bank Mandiri's digital services provide significant added value for customers and companies, are rare in the market, and are difficult for competitors to imitate thanks to investments in cutting-edge technology. Bank Mandiri has a supportive organization, with a structure and culture of innovation that allows for optimal utilization of digital resources. The strategic implications of this digital advantage include increased customer loyalty, expanded customer base, and increased operational efficiency. By continuing to invest in technology and expand the digital ecosystem, Bank Mandiri has the potential to maintain its competitive advantage and become a leader in digital transformation in the Indonesian banking industry.